Analisa Numerik Perilaku Penampang Baja Canai Dingin Unlipped Channel Akibat Beban Aksial - Budiman Budiman (JURNAL TEKNIK SIPIL CENDEKIA (JTSC), 2023)
The development of construction material that is more efficient and friendly continued by researchers. Steel is a material that is widely used in construction, especially hot-rolled steel, the use of cold-formed steel is an innovation where cold-formed steel has more advantages than hot-rolled steel. Many studies of cold-formed steel sections due to applied loads have been carried out to observe the behavior and capacity of the sections. An unlipped channel is a steel section that can be used in buildings, cold-formed steel unlipped channel will be subjected to an axial load to see the behavior and capacity of the section which is the aim of this study. In this study, a numerical analysis of cold-formed steel sections will be performed using the finite element method through ABAQUS software, the numerical analysis is committed based on existing research in the literature. The Sectional capacity resulting from the numerical analysis will be compared with the effective width method approach based on SNI 7971-2013.